Modernisasi Aktivisme Filantropi NU di Indonesia - Sofuan Jauhari (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The modernization of Nahdlatul Ulama (NU) philanthropic activism in Indonesia emerged as a response to the dynamics of complex social and economic change. NU as a traditionalist Islamic organization utilizes the Aswaja principle (Ahlussunnah wal Jamaah) which focuses on moderation, justice, tolerance, and balance to adapt its philanthropic approach. This study highlights how NU strengthens local values and Islamic traditions while innovating through philanthropic programs such as Gerakan Koin NU, NUSAQU, ASTANA, and the Bank Sampah Nusantara environmental program. With a moderate and inclusive approach, NU has succeeded in responding to the needs of modern society without neglecting tradition, creating a balance between spiritual, social, and environmental demands. This study uses qualitative methods through literature studies to explore NU's contribution to modernizing Islamic philanthropy, showing the relevance of this religious organization as an agent of adaptive and sustainable social change.